On metric dimension of P(n, 2)ʘK1 graph. (17th February 2021) - Ahmad, Zubair; Chaudhary, Maqbool Ahmad; Baig, Abdul Qudair; Zahid, Manzoor Ahmad
Abstract: For a connected graph G, a subset W = { w 1, w 2, w 3,  … , wξ } of the vertices of G is the resolving set for G if for a, b ∈ V ( G ), we have d ( a, wξ ) ≠ d ( b, wξ ) for all wξ ∈ W . Metric basis for G is the minimum number of vertices in W and metric dimension is the cardinality of such a set denoted by β ( G ). In this paper we compute the metric dimension of P ( n, 2)ʘ K 1 .